FUCOIDAN NANOENCAPSULATION FROM BROWN ALGAE (Sargassum polycystum) AS A POTENTIAL MARINE IMMUNOMODULATORY AGENT - Purwanto, Ungsari Rizki Eka; Ikasari, Endang Diyah; Bagiana, I Kadek; Kusmita, Lia; Trisnayanthi, Ni Nyoman Ayu Indah; Mudianta, I Wayan; Prasetijo, Rahmadi (Jurnal Ilmiah Farmako Bahari, 2024)
The quest for better and more effective treatments has encouraged the search for therapies derived from natural sources to obtain effective immune therapy, considering that several pandemics have arisen caused by viruses. Developing fucoidan from brown algae in drug encapsulation as an immunomodulator could be more promising. This study aimed to produce nanoencapsulation loaded with fucoidan-purified extract from brown algae and to evaluate the influence of nanoencapsulation formulation on the immunomodulatory activity of fucoidan. Fucoidan was obtained from brown algae and extracted by hot aqueous, followed by ethanol purification. Nanoencapsulation of fucoidan purified extract was prepared using the ionic gelation method. The carbon clearance method was carried out for the immunomodulatory activity test of the nanoencapsulation of fucoidan purified extract. Nanoencapsulation of fucoidan purified extract with the optimum composition of maltodextrin 9.9% and S-TPP 0.1% (1:5) resulted in particle size of 715.4 nm, zeta potential -0.1 mV, pH 7.54, transmittance 97.54%+0.08, and entrapment efficiency 89.94%+0.17. The carbon clearance test showed that the nanoencapsulation of fucoidan was a strong immunostimulant with a phagocytosis index of 1.65. The development of nanoencapsulation could increase the phagocytosis index of fucoidan purified extracts from brown algae. Further molecular studies are needed to demonstrate the molecular activity of this preparation as an immunomodulator.